A Network Meta-Analysis of Two Doses of Recombinant Human Thrombopoietin for Treating Sepsis-Related Thrombocytopenia. (30th December 2022) - Chen, Dandan; Hou, Yu; Wei, Chaochao; Cai, Xingjun
Abstract : Previous studies suggest that sepsis remains a common critical illness with a global incidence of 31.5 million. The aim of this study was to evaluate the comparative therapeutic value of recombinant human thrombopoietin (rhTPO) in treating sepsis patients with thrombocytopenia. We conducted a comprehensive electronic search of PubMed, EMBASE, the Cochrane Library, and CNKI from its inception through December 31, 2021. Thirteen randomized controlled trials (RCTs) involving 963 patients were included. Network meta-analyses showed that rhTPO 300 U/kg/day and rhTPO 15000 U/day significantly increased the platelet (PLT) levels on the 7 th day and decreased the requirement of transfusion of red blood cells (RBCs), plasma, and PLT compared with IVIG and NAT. SUCRA showed that rhTPO 300 U/kg/day ranked first in terms of 28-day mortality (85.5%) and transfusion, including RBC (88.7%), plasma (89.6%), and PLT (95.2%), while rhTPO 15000 U/day ranked first for the length of the intensive care unit (ICU) stay (95.9%) and PLT level at day 7 (91.6%). rhTPO 300 U/kg/day may be the optimal dose to reduce 28-day mortality and transfusion requirements. However, rhTPO 15000 U/day may be the optimal dose for shortening the ICU stay and increasing the PLT level on the 7th day. However, additional studies to further validate our findings are needed.